Mismanagement of a Huge Ovarian Serous Cystadenoma in a Young Girl; a Case Report - Jila Agah; Reza Jafarzadeh Esfehani; Batool Kamalimanesh; Mojtaba Fattahi Abdizadeh; Amir Reza Jalilian (Mashhad University of Medical Sciences, 2015)
While ovarian masses are common findings in gynecology, unusually huge masses are quite rare. However, such cases can still be found today. Mismanagement of common complaints in patients can be a leading cause of facing such findings. Herein, we introduce a case of a giant ovarian cyst, which was mismanaged in a young virgin female patient. The patient had received gastrointestinal medications for months before being admitted to our clinic, given the bloating sensation and lack of any gynecologic problems. Ultrasonography disclosed a giant cyst, probably related to the ovary, originating from the pelvis and extending toward the diaphragm. After a successful surgery, the ovarian cyst, measuring 40 centimeters and weighing 8 kilograms, was removed. Pathology report revealed serous cystadenoma. Existence of such cases can be an alarming sign for physicians to manage prevalent complaints more seriously, particularly those non-responsive to treatment.